2011
DOI: 10.1177/139156141101200204
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Inflation in Sri Lanka

Abstract: A high and sustained economic growth in conjunction with low inflation is the central objective of macroeconomic policy formulation in both developed and developing countries. Further, studying inflationary processes is an important issue in the current scenario as it allows policy-makers to achieve monetary and economic targets. However, it is not an easy task, especially in developing coun-tries, where economic processes are highly unstable and volatile. The situation in Sri Lanka is not exceptional. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Applied economic research, since the last three decades, has increasingly been giving emphasis to the role of fiscal variables in determining inflation in countries concerned. In the case of Sri Lanka, few studies have examined the role of monetary factors in inflation (Bandara, 2011; Cooray, 2008; Kulatunge, 2017; Maitra & Debnath, 2015; Ratnasiri, 2011). However, the role of fiscal factors in inflation is scantly documented.…”
Section: Introductionmentioning
confidence: 99%
“…Applied economic research, since the last three decades, has increasingly been giving emphasis to the role of fiscal variables in determining inflation in countries concerned. In the case of Sri Lanka, few studies have examined the role of monetary factors in inflation (Bandara, 2011; Cooray, 2008; Kulatunge, 2017; Maitra & Debnath, 2015; Ratnasiri, 2011). However, the role of fiscal factors in inflation is scantly documented.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the univariate ARIMA(1, 1, 2) was selected as the best model using adjusted R-squared statistics. (Bandara, 2011)used the VAR models to forecast the inflation rate of Sri Lanka using the monthly mean historical data . (Jere, 2016) used the univariate time series models to forecast the inflation rate of Zambia by using Holt's Exponential Smoothing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on several research findings concerning the factors influencing inflation, the following are identified as follows. Bandara (2011) shows the factors influencing inflation in Sri Lanka from 1993 to 2008 using VAR models and the Granger causality method. The findings show that money supply, exchange rate and GDP exhibit significant information to explain the inflationary trends in Sri Lanka.…”
Section: Literature Reviewmentioning
confidence: 99%